The Social Sciences in the Asian Century - Johnson, Carol; Mackie, Vera; Morris-Suzuki, Tessa (ANU Press, 2015)
In this collection of essays, we reflect on what it means to practise the social sciences in the twenty-first century. The book brings together leading social scientists from the Asia-Pacific region. We argue for the benefit of dialogue between the diverse theories and methods of social sciences in the region, the role of the social sciences in addressing real-world problems, the need to transcend national boundaries in addressing regional problems, and the challenges for an increasingly globalised higher education sector in the twenty-first century. The chapters are a combination of theoretical reflections and locally focused case studies of processes that are embedded in global dynamics and the changing geopolitics of knowledge. In an increasingly connected world, these reflections will be of global relevance